PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS DAN KEMANDIRIAN BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN RECIPROCAL TEACHING - Maryunah Maryunah; Edi Syahputra; M. Amin Fauzi (JURNAL TEMATIK, 2019)
The purpose of this study is to improve mathematical communication skills with the independence of student learning by using a reciprocal teaching learning model. This research is a quasi-experimental study. The population in this study consisted of all vocational students in Percut Sei Tuan District, by taking a sample of Gema Buwana Private Vocational School. Data analysis was carried out with Anava two paths. The results of this study indicate that (1) Increasing the mathematical communication skills of students taught with reciprocal teaching learning models is higher than students taught with conventional learning, (2) Increasing the learning independence of students taught with reciprocal teaching learning models is higher than students taught with conventional learning, (3) There is no interaction between learning models with students 'initial mathematical abilities to increase students' mathematical communication skills, (4) There is no interaction between learning models with students 'initial mathematical abilities towards increasing students' learning independence.